Model Tata Kelola Institusi Terkait Pendanaan, Pembiayaan, dan Pengelolaan Infrastruktur Air di Provinsi Jawa Tengah Indonesia - Deni Ramdani; Muhamad Wahyudi (Jurnal Bisnis dan Ekonomi, 2019)
Institutional governance and infrastructure reform combined with the policy package constitute a restructuring of private public partnerships. The challenges of institutional and water governance as a form of innovation answer the challenges of an increasingly competitive market, the needs of consumers, and investors. A sluggish investment climate will turn into a prospectus with a comprehensive funding model that meets the challenges faced by current and growing imbalances. The results of the study identified a governance model for funding, financing and developing infrastructure projects in the province of Central Java, innovation in funding models as a hybrid model with Public Private Partnership (PPP) partnerships for future water management and development that can consolidate the water resources of the provinces of Central Java and nationally, infrastructure functions and capabilities are the foundation for the establishment of water supply services.